Alterations in surface hydrophobicity of Acinetobacter baumannii induced by meropenem - Hostacká, A (Folia microbiologica, 1999)
Six strains of Acinetobacter baumannii out of eleven strains tested revealed a strong hydrophobic character. This was demonstrated by adherence of bacteria to xylene in the range of 90-94%. Changes in surface hydrophobicity of these strains were studied after treatment with meropenem at subinhibitory concentrations (sub-MICs) (1/4, 1/8, 1/16 or 1/32 of the MICs). All strains showed a reduced adherence to xylene after the action of meropenem at 1/4 or 1/16 of the MICs. Hydrophobicity of the treated bacteria was decreased to 1.3-70% (1/16 of the MICs) or to 12-86% (1/4 of the MICs), depending on the strain. A decrease in surface hydrophobicity of three strains was also observed after their exposure to meropenem at 1/8 of the MICs (to 18-71% of the control values). Meropenem at 1/32 of the MICs practically did not affect bacterial hydrophobic properties, with the exception of one strain.
Keywords: meropenem; thienamyciny; Bacterial Adhesion; Acinetobacter; povrchové vlastnosti; Microbial Sensitivity Tests; Xylenes; Thienamycins; bakteriální adheze; antibiotická rezistence; xyleny; Drug Resistance, Microbial; Meropenem; mikrobiální testy citlivosti; Surface Properties